Central Nervous System Intraoperative Cytopathology - Lacruz, César R. (Essentials in Cytopathology,, 2018)
This book covers the full spectrum of benign and malignant conditions of the central nervous system with emphasis cytomorphologic characteristics and differential diagnosis. The volume is heavily illustrated and contains useful algorithms that guide the reader through the differential diagnosis of common and uncommon entities encountered in the field of intraoperative neuro-cytopathology. Central Nervous System Intraoperative Cytopathology serves as a valuable reference for pathologists, cytopathologists, and fellows and trainees by providing a concise guide of the current critical information needed to recognize, understand, and interpret this demanding field of surgical neuropathology.